The myth of LGBTQ mobilities: framing the lives of gender- and sexually diverse Australians between regional and urban contexts. Issue 3 (3rd March 2020) - Cover, Rob; Aggleton, Peter; Rasmussen, Mary Lou; Marshall, Daniel
Abstract: Gender- and sexually diverse youth are often represented in popular discourses through concepts of movement and mobility. Conceptual stories of LGBTQ youth transitions to adulthood in particular are marked by narratives of movement from regional (rural and/or small towns) to major urban areas. Although not wholly outside lived experience, a cultural myth that portrays the experience of gender- and sexually diverse young people entering into 'adulthood' via such mobility continues to circulate in scholarship, popular media, personal accounts of coming out, support resources and self-help guidance documents. This paper draws on a recent study of gender and sexual diversity, support and belonging to examine instances of LGBTQ youth mobility in relation to participant interviews and focus groups undertaken in an Australian project examining two generations of sexually diverse subjects' views on growing up, support and belonging. Participants differed generationally in how they experienced mobility from regional to urban settings, demonstrating that contemporary real-world accounts of such mobility are complex, nuanced and diverse and that the felt 'expectation' that one should migrate to a city in order to live a full gender- or sexually diverse life has waned among young people in the more recent generation.